Phytochemical Investigation, Proximate Composition, Acute Toxicity, Anti-Inflammatory and Antinociceptive Activities of Extracts of Caesalpinia Pulcherrima Linn Flower - Uadia, Jeremiah Ogboma; Nnamdi, Emeka Kingdom; Chigozie, Nnadozie; Ndubisi, Valerie Ifeanyi; Ogbeide, Osahon Kennedy (Walisongo Journal of Chemistry, 2023)
The management and treatment of inflammation and pains have continued to gain increasing interest in recent times due to the challenge they pose to health. The study evaluated the phytoconstituents, proximate content, acute toxicity, antioxidant, anti-inflammatory, and antinociceptive properties of Caesalpinia pulcherrima flower extracts using different solvents. The bioactive chemical constituents, acute toxicity, and antioxidant property were investigated via standard methods while the anti-inflammatory and analgesic activities were determined using formalin-induced inflammation and acetic acid-induced writhing methods respectively. Phytochemicals determined were alkaloids, glycosides, saponins, tannins, phenolics, terpenoids, and steroids. The moisture, crude fibre, crude lipid and total ash content determined were 6.20 ± 0.01%, 15.00 ± 0.07%, 1.80 ± 0.03% and 7.00 ± 0.00% respectively. The n-hexane extract possessed the chief % inhibition (86.49 ± 0.30) and for ascorbic acid 88.29 ± 0.00 at 500 μg/mL extract from the antioxidant study. The acetone extract displayed the greatest significant anti-inflammatory potential at both 100 and 200 mg/kg dose at four hours, being the most effective and there exist a momentous reduction at p 0.05 in the writhes’ number in a manner depended on dose in the acetone and n-hexane extracts. At 5000 mg/kg, there was 100% mortality when the crude extracts were orally administered to the Swiss mice. This study ratifies that Caesalpinia pulcherrima flower extract is a potential spring of phytomedicine which could be applied for managing of inflammation, pain and oxidative stress-related infections but higher dosages could potentially be lethal.